LAND SUBSIDENCE SUSCEPTIBILITY MAPPING USING GEOGRAPHIC INFORMATION SYSTEM (GIS) IN RONGKOP SUB - DISTRICT, GUNUNG KIDUL REGENCY, YOGYAKARTA SPECIAL PROVINCE, INDONESIA - , KHAYKEO KEOKHAMPHUI ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Rongkop area is considered to be a susceptible area to land subsidence occurrence due to the interactions of unfavorable conditions such as morphology, weak engineering properties of lithology, structural geology. Moreover, there are significant numbers of sinkhole and land subsidence traces which are found in the area and those land subsidence have provoked several considerable disasters to the habitants living in the region. The main objectives of this research are to assess land subsidence based on the intrinsic factors, to know the type or mechanism of land subsidence in Rongkop Sub- Distict, Gunung kidul Regency and to know land subsidence susceptibility map in this area. In this study, land subsidece susceptibility map was developed based on four parameters such as slope degree, lithology, relative relief, and distance to lineaments of valley. Supported by GIS software, scores given to each class of parameters were done according to land subsidence density, a ratio between the area occupied by the land subsidence pixels on a class of a certain parameter and the total area of that class, changed into percentage. Meanwhile, weights for all parameter were determined by using opinion-based scores adopting a criterion of Analytic Hierarchy Process (AHP). Within the process, a pair-wise comparison matrix was developed to facilitate the comparison as only two parameters are allowed to conduct the comparison at a time. By reclassifying the susceptibility index value, the susceptibility zones namely very high, high, moderate, low, and very low can be draw. The results reveal that the hazard zones were located along the valleys showing the coincidence with the sinkholes locations. This research outcome will beneficially provide the recommendation for appropriate landuse management in the land subsidence suscebtible area as well as identification the most potentially susceptible area for land subsidence mitigation.